Implementasi Teori Interaksi Simbolik Player Saat Memainkan Game Mobile Legends - Sonia, Widiana; Pandrianto, Nigar (Kiwari, 2024)
The researcher prepared a list of questions for informants where interviews with informants in the Mobile Legend player category were conducted at the Central Park mall and interviews with academics category informants were conducted at Tarumanagara University. Data collection through interviews, observation, and case studies. From the results of these interviews, Mobile Legends players also use the features available in Mobile Legends to communicate between players during gameplay and apply interpersonal communication and symbolic interaction theory. Symbolic interaction can occur when language or behavior or nonverbal images or symbols have the same meaning, but when the resulting meanings are different, this does not rule out the possibility of symbolic interaction. By playing Mobile Legends for a long time, besides making new friends in cyberspace, or expanding social networks, players still maintain good relations with old players, players also feel that their leadership skills are developing and are useful for making decisions in the real world, or work environment. The author hopes that the results of this study will not be misused. Peneliti menyiapkan daftar pertanyaan untuk informan dimana wawancara dengan informan kategori Mobile Legend player dilakukan di mall Central Park dan wawancara dengan informan kategori akademisi dilakukan di Universitas Tarumanagara. Pengumpulan data melalui wawancara, observasi dan studi kasus. Dari hasil wawancara tersebut, para pemain Mobile Legends juga menggunakan fitur yang tersedia dalam Mobile Legends untuk berkomunikasi antar player selama bermain game dan menerapkan komunikasi interpersonal serta teori interaksi simbolik. Interaksi simbolik dapat terjadi ketika bahasa atau perilaku atau citra atau simbol nonverbal memiliki makna yang sama, tetapi ketika makna yang dihasilkan berbeda, hal ini tidak menutup kemungkinan terjadinya interaksi simbolik. Dengan bermain Mobile Legends dalam waktu yang lama, selain menambah teman baru di dunia maya atau memperluas jejaring sosial, pemain tetap menjaga hubungan baik dengan pemain lama, pemain juga merasa kemampuan kepemimpinan mereka berkembang dan berguna untuk mengambil keputusan di dunia nyata, atau lingkungan kerja.